2017
DOI: 10.1038/tp.2017.19
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia-like phenotypes in mice with NMDA receptor ablation in intralaminar thalamic nucleus cells and gene therapy-based reversal in adults

Abstract: In understanding the mechanism of schizophrenia pathogenesis, a significant finding is that drug abuse of phencyclidine or its analog ketamine causes symptoms similar to schizophrenia. Such drug effects are triggered even by administration at post-adolescent stages. Both drugs are N-methyl-d-aspartate receptor (NMDAR) antagonists, leading to a major hypothesis that glutamate hypofunction underlies schizophrenia pathogenesis. The precise region that depends on NMDAR function, however, is unclear. Here, we devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Although early studies reported increased locomotor activity in mice expressing 5% of normal levels of GluN1 22 , recent investigation showed that locomotor activity in these mice is comparable to the locomotor activity of wild-type littermates in a familiar environment 57 . In fact, locomotor activity is not directly correlated to the levels of GluN1, as increased locomotor activity has been reported to be associated with both increase 58 or decrease 59 of GluN1 levels. PCP is often used to model aspects of schizophrenia, inducing their prominent psychotomimetic effects by blocking neurotransmission at NMDAR-type glutamate receptors and inducing schizophrenia-related behaviors 16 , 60 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Although early studies reported increased locomotor activity in mice expressing 5% of normal levels of GluN1 22 , recent investigation showed that locomotor activity in these mice is comparable to the locomotor activity of wild-type littermates in a familiar environment 57 . In fact, locomotor activity is not directly correlated to the levels of GluN1, as increased locomotor activity has been reported to be associated with both increase 58 or decrease 59 of GluN1 levels. PCP is often used to model aspects of schizophrenia, inducing their prominent psychotomimetic effects by blocking neurotransmission at NMDAR-type glutamate receptors and inducing schizophrenia-related behaviors 16 , 60 64 .…”
Section: Discussionmentioning
confidence: 99%
“…A subtype of glutamate receptors named N-methyl-D-aspartate receptors (NMDARs), which mediates excitatory neuronal transmission, plays a critical role in brain functions [68]. Neurological and psychiatric disorders such as stroke, schizophrenia and certain forms of autism can be attributed to dysfunctional NMDARs [69, 70]. The 24S-hydroxycholesterol, a brain cholesterol metabolite, is a positive modulator of NMDARs when administered exogenously [71, 72].…”
Section: Cholesterolmentioning
confidence: 99%
“…Immunohistochemistry was performed according to the method described elsewhere (Yasuda et al, 2017). Mouse monoclonal antibody against calbindin D28k (#300) was purchased from Swant and rabbit polyclonal antibody against GFP (MBL598) was purchased from MBL.…”
Section: Immunohistochemistrymentioning
confidence: 99%